DIAGNOSIS OF ORF IN WEST AFRICAN DWARF GOATS IN UYO, AKWA IBOM STATE, NIGERIA - Adedeji, Adeyinka Jeremy; Maurice, Nanven Abraham; Wungak, Yiltawe Simwal; Adole, Jolly Amoche; Chima, Nneka Chineze; Woma, Timothy Yusufu; Chukwuedo, Anthony Amechi; Shamaki, David (African Journal of Infectious Diseases (AJID), 2017)
Background: Sixty (60) male West African Dwarf goats were reported with clinical signs of enlarged lymph nodes, scabs on the mouth, nose and ears. Two of the goats died and post mortem examination reveals enlarged submandibular lymph nodes and vesicular lesions on the tongue. Clinical diagnosis of Orf has been reported in Nigeria but this report is the confirmatory diagnosis of Orf in a suspected outbreak in an experimental farm in Uyo, Akwa Ibom State, Nigeria using molecular techniques. Materials and Methods: Scabs, spleen and lymph node samples from goats suspected to have died from Orf were collected, transported on ice to the laboratory and homogenized. The DNA was extracted using QIAmp DNA minikit (Qiagen) according to the manufacturer’s instructions. Orf virus (ORFV) was amplified using published ORFV specific primers by PCR. Results: Morbidity and mortality were 100% and 3.3% respectively, while ORFV was detected by PCR. Diagnosis of Orf was confirmed based on clinical signs of enlarged lymph nodes, scabs on the mouth, nose and ears, necropsy findings of enlarged submandibular lymph nodes and vesicular lesions on the tongue and PCR results. Conclusion: This may be the first report of molecular diagnosis of Orf in Nigeria. The 100% morbidity and 3.3% mortality rate is higher than previously reported thus Orf is becoming of greater economic importance than previously thought. It is therefore recommended that routine laboratory diagnosis of Orf be carried nationwide to determine the prevalence of Orf in Nigeria.